Influence of parents’ sanitary education level on health state and buccal hygiene of children with mental retardation - Benavente Lipa, Lourdes Ángela (2007)
The purpose of this investigation was to evaluate the influence of parents on the level of sanitary education on buccal health and buccal hygiene on children with slight or moderate retardation. An analytic type and cross-sectional investigaton was made. The sample was conformed by 58 children of both sexes from slight or moderate mental retardation between 6 and 14 years of age, who were accompanied by their parents. The evaluation of the level of sanitary education on buccal health of the empowered parents or parents, was made by means of a semi-structured questionnaire, classifying them in two groups, low and average levels, the children were selected intentionally and equitably at the levels of sanitary education of their parents and clinically examined at natural light, using the following epidemiologist factors: Decay (CPOD-ceod). Greene and Vermillion modified dental plaque (IHOS); Löe and Silness Gingival modified rate(IG). When relating the level of sanitary education on buccal health of parents to the state of health and buccal hygiene of the children with mental retardation, it was observed that 62,1% of the children whose parents had low sanitary education on buccal health they presented a bad state of health and bad buccal hygiene in comparison with 65,5% of the children whose parents had an average level of sanitary education on buccal health which presented a state of health of regular buccal hygiene, there was a statistically significant difference when applying test x2 (p=0.036). Therefore it is deduced that the level of sanitary education on buccal health of parents, is related to the state of health and buccal hygiene of the children with slight or moderate mental retardation studied.